Marginal intra-industry trade and adjustment costs:the Australian experience - Thorpe, Michael (2011)
The objective of this research is to investigate labour market adjustment associated with changes in Australia’s trade pattern over the period 1992-2000. Specifically the focus is on the so-called smooth adjustment hypothesis (SAH) which posits that, compared with interindustry trade, intra-industry trade (IIT) expansion is associated with relatively lower factor adjustment costs. A dynamic panel data approach (GMM-System) is employed. We find that there is a negative correlation between changes in employment and increased IIT. This result provides support for the SAH. Given the rise in IIT as a proportion of Australia’s overall trade during the period under review, the adjustment in labour markets stemming from trade liberalisation at that time is likely to have been less than otherwise expected.